Tourism After Lockdown: Will Business Travel Maintain Popularity? - UKHINA, Tatiana Viktorovna; MAIDANEVYCH, Yulia Petrovna; ABDIMOMYNOVA, Almakul Shakirbekovna; STEPANOVA, Diana Igorevna; ZAMBINOVA, Gulmira Kairbaevna (Journal of Environmental Management and Tourism, 2021)
Business travel is an exceptional phenomenon of the 21 st century and a key segment of the hospitality market. Business travel has filled a niche in the tourism business, easing the problem of seasonality and attracting foreign tourists. This field can produce a lot of economic results for the development of the global economy. Business travel and a country's economy are closely connected as the former plays an important part in improving the country's rating. The article deals with the consequences of the pandemic for business travel and features of business travel during the pandemic. Based on an expert survey, the authors determine the promise of implementing virtual events in the industry of meetings, incentives, conferences, and exhibitions in the pandemic; the prospects and timeframes for the recovery of various segments of the industry as well as the key imperatives for its recovery after the restrictions are lifted. The authors analyze the operational prospects of the companies working in the business travel segment before and after the restrictions are lifted. It is concluded that after the restrictions are lifted, business travel will maintain its popularity if the necessary measures are taken to restore the industry and use the latest innovative technologies.